Analisis Simulasi Sistem Penunjang Keputusan: Model Matematis Dengan Pendekatan Goodness-of Fit Berbasis Structural Equation Model - Achmad Udin Zaelani; T. Husain; Agus Budiyantara (SMARTICS Journal, 2020)
Analysis of decision support systems derived using a mathematical models with goodness-of-fit approach can confirm or produce the results of a goodness of fit concordance. The estimation method used in this study use a maximum likelihood estimation of indicators consists of financial liquidity ratio's such as current ratio's, quick or acid test ratio's, cash ratio's and net-working capital ratio's which are tested for validity and evaluation of goodness-of fit criteria. Decision support systems based on structural equation modeling (SEM) which are derived into mathematical models (quantitative) can explain the complexity of the relationship between the goodness-of fit using a structural equation modeling (SEM) based approach